2016
DOI: 10.1038/srep35868
|View full text |Cite
|
Sign up to set email alerts
|

Soluble P-selectin rescues viper venom–induced mortality through anti-inflammatory properties and PSGL-1 pathway-mediated correction of hemostasis

Abstract: Venomous snakebites are lethal and occur frequently worldwide each year, and receiving the antivenom antibody is currently the most effective treatment. However, the specific antivenom might be unavailable in remote areas. Snakebites by Viperidae usually lead to hemorrhage and mortality if untreated. In the present study, challenges of rattlesnake (Crotalus atrox) venom markedly increased the circulating soluble P-selectin (sP-sel) level, but not P-selectin (P-sel, Selp−/−) mutants, in wild-type mice. Because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 68 publications
1
37
0
Order By: Relevance
“…35 The anti-P-sel Ig showed an ameliorative effect in our previous report using a viper venom-challenged mouse model, in which anti-P-sel Ig ameliorated snake venom-induced inflammation, coagulant defects, and mortality. 36 To investigate whether the anti-inflammation property of sP-sel is also involved in the rescue, we further examined the effects of anti-P-selneutralizing antibody treatment, as both anti-P-sel-neutralizing antibodies and recombinant sP-sel suppress inflammation by blocking leukocyte infiltration to the inflamed tissues through the P-sel and P-sel ligand interaction. 35 We observed that, similar to control Ig, the anti-P-sel-neutralizing antibody did not rescue LTtreated mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…35 The anti-P-sel Ig showed an ameliorative effect in our previous report using a viper venom-challenged mouse model, in which anti-P-sel Ig ameliorated snake venom-induced inflammation, coagulant defects, and mortality. 36 To investigate whether the anti-inflammation property of sP-sel is also involved in the rescue, we further examined the effects of anti-P-selneutralizing antibody treatment, as both anti-P-sel-neutralizing antibodies and recombinant sP-sel suppress inflammation by blocking leukocyte infiltration to the inflamed tissues through the P-sel and P-sel ligand interaction. 35 We observed that, similar to control Ig, the anti-P-sel-neutralizing antibody did not rescue LTtreated mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…20,42 In addition, it is also shown that increased levels of circulating sP-sel play a protective role when mice are under hemorrhage or hypoxic stress. 36,43 Therefore, increased endogenous sP-sel levels may theoretically have a physiologic role of protecting against hemorrhage and ischemic conditions through correcting hemostasis. Moreover, increased sP-sel levels have been observed in various hemorrhagic diseases such as dengue hemorrhagic fever, 39 immune thrombocytopenia, 44,45 and subarachnoid hemorrhage 46 ; however, the role of sP-sel in these disorders remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Snake toxins have also been expressed into E. coli and this approach has allowed the characterization of toxins with anti-thrombotic [13], anticancer [14], anti-inflammatory [15], antimicrobial activities [16] as well as fused toxins for the development of serotherapy against envenomation [17]. However, when a recombinant protein is synthesized in E. coli , the microenvironment is different from that of the original source, which may lead to protein aggregation, known as inclusion bodies [18].…”
Section: Introductionmentioning
confidence: 99%